Microbial characterization of on-farm produced bio-enhancers used in organic farming - RAM, R A; SINGHA, ATUL; VAISH, SUPRIYA (The Indian Journal of Agricultural Sciences, 2018)
Different bio-enhancers commonly used in organic production of various crops were prepared for microbial characterization. Panchagavya had been utilized since long time by the farmers to provide nutrients to the plants and soil micro-organisms. Microbial analysis of bio-enhancers revealed that Panchagavya contained highest number of total bacteria (6.25 × 109 cfu/ml) as compared to Jeevamrita (3.24 × 109 cfu/ml), biodynamic liquid pesticide (2.27 × 109 cfu/ml) and Amritpani (5.49 × 109 cfu/ml). Panchagavya had also higher number of Pseudomonas (4.7 × 109 cfu/ml), Rhizobium (2.43 × 109 cfu/ml), Azotobacter (1.4 × 109 cfu/ml) and Azospirillum (1.03 × 105 cfu/ml). Fungi population was highest in Jeevamrita (1.20 × 107 cfu/ml) as compared to biodynamic liquid pesticide (2.64 × 106 cfu/ml), Amritpani (0.46 × 105 cfu/ml) and Panchagavya (0.20 × 105 cfu/ml). Actinomycetes, Pseudomonas, p-solubilizing microbes, Azotobacter and Azospirillum population were highest in biodynamic liquid pesticide (1.37 × 108, 3.28 × 108, 8.50 × 106, 2.00 × 106 and 1.40 × 105 cfu/ml). Similarly, gram positive bacteria, gram negative bacteria and Rhizobium were highest in Jeevamrita (1.60 × 108, 2.20 × 108, 7.51 × 107 cfu/ml). Amritpani had higher number of actinomycetes (1.31 × 107 cfu/ml), gram negative bacteria (1.35 × 108 cfu/ml) and p-solubilizing microbes (4.80 × 106 cfu/ml). Among all bio-enhancers, Panchagavya was rated most effective bio-enhancer followed by biodynamic liquid pesticide, Jeevamrita and Amritpani. Results reveal that these bio-enhancers could play a potent source of beneficial microbes which could improve soil fertility, crop productivity and produce quality.